Analiza przyczyn i czasu pozostawania na bezrobociu - Ulman, Paweł (The Analysis of the Determinants and Duration of Unemployment, 2009)
The paper presents the results of the analysis of unemployment in Poland in the context of two facts: unemployment experience and unemployment duration. The logit model was used to identify the determinants which my influence the probability of being unemployed, whereas the Cox proportional hazard model was used in the analysis of unemployment duration. Statistical data was taken from statistical database which had been created in 2007 for the research for Social Diagnosis series. The results indicate the universality of some common characteristics of the unemployed, which determinate their situation in the labour market, but the influence of these factors does not necessarily have to be the same in both areas of the analysis carries out. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 418-426